2014
DOI: 10.1590/1983-1447.2014.03.45772
|View full text |Cite
|
Sign up to set email alerts
|

Hygiene and motivation factors of nursing work in a cardiology ward

Abstract: Hygiene and motivation factors of nursing work in a cardiology ward ABSTRACTThe present study aimed to identify hygienic and motivational factors in the nursing work according to the Two-Factor Theory, as well as their relation with professional satisfaction/dissatisfaction. This exploratory-descriptive study involved nine nurses from the cardiology ward of a hospital in the interior of the State of São Paulo, between August and September 2013. A self-applied questionnaire was used, including open and closed q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
1
4
0
1
Order By: Relevance
“…(27) In other studies in which inappropriate physical structure, absence of materials and equipment, lack of HR and lack of institutional stimulus were also found, these factors lead to improvisations and reduce the quality of care provided. (23,28) The results of this research converge with a study developed in South Africa, in which the authors also showed that the reasons for absenteeism in nursing are related to professional (long working hours, low pay, insufficient number of professionals, etc. ), personal (family reasons, disease, etc.)…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…(27) In other studies in which inappropriate physical structure, absence of materials and equipment, lack of HR and lack of institutional stimulus were also found, these factors lead to improvisations and reduce the quality of care provided. (23,28) The results of this research converge with a study developed in South Africa, in which the authors also showed that the reasons for absenteeism in nursing are related to professional (long working hours, low pay, insufficient number of professionals, etc. ), personal (family reasons, disease, etc.)…”
Section: Discussionsupporting
confidence: 79%
“…(22) Within this logic, in research, it is verified that lagged wages generate dissatisfaction and, considering the contemporary reality, lead workers to engage in more than one employment bond, causing work overload, stress and impact on quality of life, as well as, in many cases, illness and leave from professional functions. (23,24) After the creation of the Secretariat of Health Work and Education Management (SGTES) in 2003, the MS is active in the creation and execution of the Basic Operational Standard of Human Resources (NOB / RH-SUS), which guides the development of HR policies in the SUS, in the three (municipal, state and federal) management spheres; and is divided into four dimensions, namely: Work Management in SUS, SUS Worker Development, SUS Occupational Health and Social Control of Work Management in SUS. In a study, it is reported that the Work Management dimension has three indicators and that, in one of these indicators, Quality of the Bond, tenured workers have greater guarantees and job benefits, being exposed to less job insecurity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, motivation was very low among health workers who worked more frequent night shifts or encounter a heavy workload [62]. Moreover, inappropriate working conditions can lead to dissatisfaction with the organization as a whole [70].…”
Section: Working Conditionsmentioning
confidence: 99%
“…Professionals who have worked at the same institution for years have more experience in the routine, positively impacting interpersonal relationships and resolving disagreements between team members [ 18 , 20 ], and also decreasing the probability doubts in relation to diagnostic and therapeutic approaches [ 26 ]. In addition, health professionals who worked for 21 years or more had a better perception of PSC [ 29 ], whereas other health professionals with 6 to up to 10 years of experience had a better perception of PSC than professionals with more time of experience [ 30 ].…”
Section: Discussionmentioning
confidence: 99%